Icts in education: an analysis in argentine university - Novomisky, Sebastián (2019)
Given the changes generated by digital technologies in the ways of building knowledge, the role of educational institutions is fundamental in the reconfiguration of their teaching practices. This article aims to reveal the positions of university professors in the face of digital innovation and compare them with proposals for professional updating. The methodological design enables to conduct an exploratory study on 45 professors from the National University of La Plata (UNLP), Argentina, using an online questionnaire about the uses, practices and perceptions assigned to teaching technologies. In addition, three training proposals implemented by said academy are selected, as an observation unit, and a systematic description of such initiatives is carried out. From the articulation between the demands and teaching positions, and the performance and proposal returns, provisional conclusions are obtained: even though professors maintain a recurrent link with digital tools, these practices diminish in front of mediations that promote more creative capacities. Although processes that critically include digital resources are evident in internal training, there are contradictions within the positions expressed by professors and the adherence to trainings. This allows to discuss the challenges that higher education faces when wanting to generate sustained and genuine innovation processes.